Intepretasi Balancing Behaviour dan Kepentingan Nasional Rusia di Kawasan Afrika 2019-2022 - Alamari, Muhammad Fauzan (Universitas Komputer Indonesia, 2024)
This article explains how the African continent, which has various natural and economic potentials but is underdeveloped, has become a region of great powers to expand its influence. This research was conducted by applying qualitative research methods with exploratory analytic designs using enhanced balancing behavior theory and the concept of national interest. It can be said, Russia has the desire to return to being a great power like the former Soviet Union, which is explicitly recognized by the international community. For this reason, Russia is present in a different way, to offset the influence of other major powers and reduce the influence of Western systems such as democracy and liberal values to develop in Africa. The approach made Africa tends to silent or not taking side to support or even gave comment about it. Therefore, it can be said that this effort was not in vain, amid of its isolation because of the Russian invasion of Ukraine, now Africa is one of its closest partners, which becomes a theater to achieve its national interests. Keywords — Africa, Military, National Interest, Russia